2008
DOI: 10.1089/acm.2008.0053
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Prescribed Herbal Medicine on Liver Function in Korea: A Prospective Observational Study

Abstract: The current study showed that ingestion of HM prescribed by KMD did not increase the frequency of abnormal LFTs, at least in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The incidence of idiosyncratic liver injury among persons who use HDS is variable. Based on limited data, the incidence of hepatotoxicity from Chinese herbs appears to be low (less than 1%) . Melchart et al .…”
Section: Epidemiologymentioning
confidence: 99%
“…The incidence of idiosyncratic liver injury among persons who use HDS is variable. Based on limited data, the incidence of hepatotoxicity from Chinese herbs appears to be low (less than 1%) . Melchart et al .…”
Section: Epidemiologymentioning
confidence: 99%
“…In Korea, Yun et al [7] and Park et al [15] reported that there some herbs, for example Ephedra sinica Stapf, Scutellaria baicalensis Georgi, Dictamnus dasycarpus Turcz., Aconitum carmichaeli Debx (= Aconitum chinense Sieb. et Zucc .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, concerns about hepatotoxicity caused by herbal medicines have been raised in several papers, but remains controversial. [3–6] Indeed, several other studies [7–10] have reported that herbal medicines are safe and, with respect to liver function, are more helpful than harmful. Given the growing prevalence of combined therapies of conventional and herbal medicines, a large-scale retrospective study was performed in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1699 patients (756 males and 943 females) were involved in these studies, and 1263 inpatients (3 studies) and 436 outpatients (3 studies). Two studies were conducted in multiple clinics (Jeong et al, 2012;Yun et al, 2009). The study characteristics are summarized in Table 1.…”
Section: Final Data Analyzedmentioning
confidence: 99%
“…Summary for incidence of herbal DILI in Korea Yun et al (2009). Outpatients on 12 Oriental clinics total: 237 (M: 78/F: 159) Total: 0.42% (1 patient, M: 1/F: 0) male/female: 1.28%/0%Paeck et al (2006) Outpatients on an Oriental clinic total: 160 (M: 120/F: 40) Total: 0% (None) 71% (12 patients, M: 10/F: 2) n male/female: 1.32%/0.21% χ² test was conducted between male and female.…”
mentioning
confidence: 99%